PENGARUH GAYA KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT KLIP PLASTIK INDONESIA KOTA TANGERANG - Fayza Cahya Eka Putri; Roni Fadli (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of leadership style and job satisfaction on employee performance at PT Klip Plastik Indonesia Tangerang City. The sample used is a saturated sample technique totaling 60 employees. Data collection techniques through primary and secondary data. The method used is quantitative with an associative approach. The results showed that Leadership Style (X₁) and Job Satisfaction (X₂) had an effect on employee performance (Y) with a regression equation of Y = 22.973 + 0.222 X₁ + 0.256 X₂ with a coefficient of determination of 41.0%. The results of hypothesis testing partially affect leadership style on employee performance with the test results t count> t table or 5.516> 1.67155 then Ho₁ rejected Ha₁ accepted. Partially job satisfaction affects employee performance with the test results t count> t table or 5,710> 1,67155 then Ho₂ is rejected and Ha₂ is accepted. The results of hypothesis testing simultaneously the value of F count> F table or 19.829> 3.159 then Ho₃ is rejected and Ha₃ is accepted. It can be concluded that the results of the study show that leadership style and job satisfaction affect employee performance at PT Klip Plastik Indonesia Tangerang City.